2018
DOI: 10.1029/2018wr022601
|View full text |Cite
|
Sign up to set email alerts
|

Generating Coherent Ensemble Forecasts After Hydrological Postprocessing: Adaptations of ECC‐Based Methods

Abstract: Hydrological ensemble forecasts are frequently miscalibrated, and need to be statistically postprocessed in order to account for the total predictive uncertainty. Very often, this step relies on parametric, univariate techniques that ignore the between‐basins and between‐lead times dependencies. This calls for a procedure referred to as sampling‐reordering, which generates a coherent multivariate ensemble from the marginal postprocessed distributions. The ensemble copula coupling (ECC) approach, which is alrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 55 publications
(101 reference statements)
0
14
0
Order By: Relevance
“…The inclusion of these uncertainties aims at improving the skill and spread of the HEPSs by introducing independent information of all the plausible atmospheric states and processes. Therefore, SREPSs are increasingly used in hydrologic prediction (Cloke and Pappenberger, 2009;Verkade et al, 2013Verkade et al, , 2017Siddique and Mejia, 2017;Benninga et al, 2017;Bellier et al, 2017Bellier et al, , 2018Edouard et al, 2018;Jain et al, 2018). Several studies have stated that probabilistic forecasts could improve decisionmaking if appropriately handled (e.g., Krzysztofowicz, 2001;Todini, 2004;Ramos et al, 2013;Antonetti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of these uncertainties aims at improving the skill and spread of the HEPSs by introducing independent information of all the plausible atmospheric states and processes. Therefore, SREPSs are increasingly used in hydrologic prediction (Cloke and Pappenberger, 2009;Verkade et al, 2013Verkade et al, , 2017Siddique and Mejia, 2017;Benninga et al, 2017;Bellier et al, 2017Bellier et al, , 2018Edouard et al, 2018;Jain et al, 2018). Several studies have stated that probabilistic forecasts could improve decisionmaking if appropriately handled (e.g., Krzysztofowicz, 2001;Todini, 2004;Ramos et al, 2013;Antonetti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A popular method is to recalibrate the model results to reproduce the climatological distribution (Madadgar et al 2014). Other postprocessing techniques include event bias correction (Smith et al 1992), LOWESS regression (Cleveland 1979), variance inflation (INFL) method (Fundel andZappa 2011, Roulin andVannitsem 2015), ensemble copula coupling (ECC) (Schefzik et al 2013, Bellier et al 2018) and quantile mapping (Wood andLettenmaier 2006, Baigorria et al 2007). Although all of them improve forecast quality significantly (Kang et al 2010), Hashino et al (2007 have shown that the choice of the optimal technique is subject to application requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Further, following the ideas of Hemri et al (2015) and Bellier et al (2018), one can combine the BMA calibrated forecasts corresponding to different locations and lead times either into temporally or both spatially and temporally coherent multivariate predictions. This can be done with the help of modern techniques such as the ensemble copula coupling (Schefzik et al, 2013) or the Gaussian copula approach (Pinson & Girard, 2012).…”
Section: Discussionmentioning
confidence: 99%